High-precision 14C measurements of parenchyma-rich Hymenolobium petraeum tree species confirm bomb-peak atmospheric levels and reveal local fossil-fuel CO2 emissions in the Central Amazon - Santos, Guaciara M.; Albuquerque, Rafael Perpetuo; Barros, Claudia Franca; Ancapichun, Santiago; Oelkers, Rose; Andreu-Hayles, Laia; de Faria, Sergio Miana; De Pol Holz, Ricardo Hernán; Brandes, Arno Fritz das Neves (My University, 2022)
Atmospheric radiocarbon (C-14) recorded in tree rings has been widely used for atmospheric C-14 calibration purposes and climate studies. But atmospheric C-14 records have been limited along tropical latitudes. Here we report a sequence from 1938 to 2007 of precisely measured C-14 dates in tree rings of the parenchyma-rich Hymenolobium petraeum tree species (Porto Trombetas, 1(?)S, 56(?)W) from the Central Brazilian Amazon. H. petraeum has discernible growth ring boundaries that allow dating techniques to be employed to produce calendrical dates. Bomb-peak tree-ring C-14 reconstruction coincides with the broader changes associated with reported values of the Southern Hemisphere atmospheric C-14 curve (SH zone 3; values within the +/- 2 sigma interval), suggesting that inter-hemispheric air-mass transport of excess-C-14 injected into the stratosphere during intensive atmospheric nuclear tests is relatively uniform across distinct longitudinal regions. From the early 1980s onwards, H. petraeum had lower C-14 values than other pantropical C-14 records. Through C-14-based estimation, we found a strong influence of fossil-fuel CO2 contributions from Porto Trombetas mining operations and shipping traffic on inland waterways. An increase of at least 6.3 +/- 0.8 ppm of fossil-fuel CO2 has been detected by C-14. Our findings invite further C-14 analyses using tree rings of tropical tree species as a potential tracer for a wide range of environmental sources of atmospheric C-14-variability.
Keywords: anthropocene; atmospheric c-14 reconstruction; bomb and post-bomb c-14 periods; parenchyma-rich woods; amazon trees; fossil-fuel emissions